An exploratory network analysis of the translation industry in the Philippines perspectives from translators in the academe - Cruz, Frances Antoinette C.; Bautista, Naidyl Isis; Cabling, Kristine (2023)
This exploratory study examines the state of translation praxis through the lens of network structure types vis-à-vis governance outcomes, focusing on policies concerning certification and compensation of translators. The institutions supporting translators and translation in the Philippines are first identified, described, and presented as a network. Surveys were then conducted on the views of translators about their concerns and working conditions. Results suggest the Philippines falls under Quadrant IV of Fawcett and Daugbjerg’s (2012) typology of governance arrangements, characterized by a network where several actors are directly and indirectly involved in the policies and environment affecting translators even when there is a dearth of regulatory policies on certification, accreditation, and compensation. Policy recommendations are put forward to address these matters.
Keywords: Educational Philosophy